Surgical ciliated cyst of the jaws: A systematic review - Hatice Lamia Tuğluoğlu Dalcı; Fatma Çağlayan (Current Research in Dental Sciences)
Cysts are fluid-filled lesions located in bone or soft tissue, surrounded by an epithelial-lined capsule. Surgical ciliated cyst (SCC) is a rare, non-odontogenic cyst lined with respiratory epithelium, formed as a result of traumatic implantation of the sinus or nasal mucosa into the jawbone especially maxilla and it was included in the latest WHO classification in 2022. The present study was aimed to systematically review the cases of surgical ciliated cysts.A literature review on the search engine Web of Science, PubMed, Google Scholar and Clinical Key was conducted, without date restrictions including search terms “surgical ciliated cyst and maxilla” or “surgical ciliated cyst and mandible”. The records were examined in detail as full text according to inclusion and exclusion criteria. Inclusion criteria; lesions that were definitively diagnosed as SCC as a result of histopathological examination. Exclusion criteria; lesions without a history of surgical procedures and not diagnosed as SCC.The total number of records generated was 150 and after the duplicates were removed, 85 records left. These records were carefully examined according to inclusion and exclusion criteria and as a result a total of 39 records and 49 cases of surgical ciliated cysts were included in the systematic review. 84% of the cases were seen in and around the maxilla, and very few were in the mandible. All of them had a history of previous surgery.SCC is not a new entity; maxillofacial radiologists, surgeons and pathologists should be familiar with the clinical, radiologic, histopathologic features and medical history of the SCC cases.